THE IMPORTANCE OF USING BOARD IN ENGLISH CLASSES - Majidova Mehrinigor (Лучшие интеллектуальные исследования, 2023)
Abstract: This article is dedicated to count importance of using board in English classes. And also aimed to give examples to English games with a board.